2005
DOI: 10.1038/sj.bjc.6602751
|View full text |Cite
|
Sign up to set email alerts
|

Joint Nordic prospective study on human herpesvirus 8 and multiple myeloma risk

Abstract: An association between human herpesvirus 8 (HHV8) and multiple myeloma (MM) has been reported, though most studies have not confirmed such association. To follow-up on a previous prospective seroepidemiological study, where HHV8 tended to associate with MM risk, we linked five large serum banks in the Nordic countries with the Nordic cancer registries and 329 prospectively occurring cases of MM were identified, together with 1631 control subjects matched by age and gender. The HHV8 seroprevalences among cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Helicobacter pylori and stomach cancer, 31 EpsteinBarr virus and Hodgkin's lymphoma, 32 non-Hodgkin's lymphoma 33 and nasopharyngeal carcinoma 34 as well as papillomaviruses and cervical, 35 anal, 36 vulvar/vaginal 37 and oropharyngeal cancer. 38 Equally important, the biobank-based prospective seroepidemiological study design has also provided clear negative results for several claimed virus-tumour associations such as herpes simplex and cervical cancer, 39 human herpes virus 8 and myeloma 40 or BKV polyomavirus and neuroblastoma. 41 Our previous negative findings regarding BKV and neuroblastoma are of relevance to the present study, as the strength of evidence associating BKV with neuroblastoma was rather similar to the evidence associating JCV with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori and stomach cancer, 31 EpsteinBarr virus and Hodgkin's lymphoma, 32 non-Hodgkin's lymphoma 33 and nasopharyngeal carcinoma 34 as well as papillomaviruses and cervical, 35 anal, 36 vulvar/vaginal 37 and oropharyngeal cancer. 38 Equally important, the biobank-based prospective seroepidemiological study design has also provided clear negative results for several claimed virus-tumour associations such as herpes simplex and cervical cancer, 39 human herpes virus 8 and myeloma 40 or BKV polyomavirus and neuroblastoma. 41 Our previous negative findings regarding BKV and neuroblastoma are of relevance to the present study, as the strength of evidence associating BKV with neuroblastoma was rather similar to the evidence associating JCV with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…HHV-8 seropositivity was 12% and 15% in cases and controls, respectively. However, they could not find any association between MM and HHV-8 seropositivity [37]. In our study, HHV-8 was not observed in patients with MM by PCR method in north east Iran.…”
Section: Discussionmentioning
confidence: 59%
“…Despite these studies, other investigators published conflicting results [22,[35][36][37][38][39][40]. Olsen et al, in United States, searched for HHV-8 in MM patients by serology, PCR, and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…HHV-8 has also been reported to be present in pemphigus vulgaris, extranodal marginal zone lymphoma of salivary gland, hemophagocytic syndrome, multiple myeloma, Kikuchi lymphadenitis, and sarcoidosis. [12][13][14][15][16][17] However, the latter list of diseases is controversial as viral detection varies among studies. [18][19][20][21] Two publications by Gó mez-Román et al, 9,10 documenting HHV-8 in lesional myofibroblasts of inflammatory myofibroblastic tumor, drew attention to the possible role of the virus in the pathogenesis of this tumor.…”
Section: Discussionmentioning
confidence: 99%